The Islamic challenge : politics and religion in Western Europe - Klausen, Jytte (Oxford University Press, 2005)
Who are Europe's Muslim leaders? How do they view Islamic integration into European society and politics? Based on 300 interviews with Muslim leaders, this innovative book tackles big questions to reveal what Muslim leaders in Europe really want and the myriad ways in which Islam can become a European religion. - ;The voices in this book belong to legislators, local officials, doctors and engineers, educators and intellectuals, lawyers and social workers, owners of small businesses, translators, and community activists. They are also all Muslims, who have decided to become engaged in political.